Small RNA sequencing data of plasma extracellular vesicles in a breast cancer screening population - Jun-luan Mo; Xi Li; Lin Lei; Xiong-shun Liang; Hong-hao Zhou; Zhao-qian Liu; Li-jun Zhang; Ji-ye Yin; Wen-xu Hong (Scientific Data)
Abstract The pathogenesis of breast cancer is still unclear. Small RNAs associated with extracellular vesicles (EVs) have been found to be involved in tumor development. It is important to explore the role of EVs small RNAs in breast cancer. In this study, we established a plasma EVS-associated small RNA dataset that included 120 women who were positive for breast cancer screening and 60 women who were negative. These small RNA included 2656 miRNAs, 728 piRNAs, and 154 tsRNAs. These data provide a reference for researchers to explore molecular diagnostic biomarkers for early breast lesions.